Good Manufacturing Practices and Documentation in Pharmaceutical Production: A Comprehensive Review - Pallavi Gorukanti; Satheesh Jogala; Narender Boggula; Sucharitha Makula (Asian Journal of Pharmaceutical Research and Development, 2025)
Good Manufacturing Practices (GMP) and thorough documentation systems are the backbone of pharmaceutical manufacturing. They ensure that every medicine produced meets strict quality, safety, and efficacy standards that patients depend on. This paper explores how GMP compliance and documentation work together in pharmaceutical production, looking at their regulatory basis, real-world applications, and strategic value in today's manufacturing landscape.The pharmaceutical industry faces unique pressures. When quality fails, patients suffer. That is why GMP exists-not as bureaucratic red tape, but as a systematic framework ensuring that medicines are made right, every single time. GMP covers everything from how facilities are designed and maintained to how employees are trained and how processes are validated.This review examines GMP fundamentals and documentation requirements across global regulatory systems. We analyze frameworks like the FDA's 21 CFR Part 211, the European Union's EudraLex Volume 4, ICH guidelines (Q7 and Q10), and WHO standards. We also dive into practical implementation-how to create effective Standard Operating Procedures (SOPs), maintain batch records, manage deviations, and handle electronic documentation systems. The paper also addresses evolving data integrity standards like ALCOA+ and how quality management principles like risk assessment and continuous improvement integrate into pharmaceutical operations.